Information about the Twelfth Conference of the Lithuanian Mathematical Society - Journal , Lithuanian Mathematical (Lithuanian Mathematical Journal, 1972)
Информация о Двенадцатой конференции Литовского математического общества Informacija apie Lietuvos matematikų draugijos Dvyliktąją Konferenciją